2020
DOI: 10.1017/neu.2020.18
|View full text |Cite
|
Sign up to set email alerts
|

Reward sensitivity, affective neuroscience personality, symptoms of attention-deficit/hyperactivity disorder, andTPH2-703G/T (rs4570625) genotype

Abstract: Objective: Reward sensitivity is an increasingly used construct in psychiatry, yet its possible inner structure and relationship with other affective variables are not well known. Methods: A reward sensitivity measurement scale was constructed on the basis of large item pool collected from birth cohort representative samples (the Estonian Children Personality Behaviour and Health Study; original n = 1238). Affective Neuroscience Personality Scale (ANPS) and the Adult Attention deficit hy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(13 citation statements)
references
References 82 publications
1
12
0
Order By: Relevance
“…The ROIS scale [28], was used to assess the relationship between reward sensitivity and measures of obesity from 9 to 33 years of age. We observed that higher Insatiability by Reward We demonstrated that Insatiability by Reward and more specifically the Giving in to Cravings subscale scores were significantly lower in female TFAP2B 4/4 homozygotes compared to heterozygotes and 5/5 homozygotes.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The ROIS scale [28], was used to assess the relationship between reward sensitivity and measures of obesity from 9 to 33 years of age. We observed that higher Insatiability by Reward We demonstrated that Insatiability by Reward and more specifically the Giving in to Cravings subscale scores were significantly lower in female TFAP2B 4/4 homozygotes compared to heterozygotes and 5/5 homozygotes.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the results cannot be extrapolated to other ethnicities. Secondly, the ROIS instrument [28], used for the assessment of reward sensitivity, was developed post hoc, applied in a Finnic language, and requires further development and characterization together with related instruments;…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations